(untitled) (Progressive Agriculture, 2013)
To study the parasitism in goats in relation to different feeding systems, 1110 goats from different areas of Jaypurhat, Tangail, Netrakona and Mymensingh districts were examined. By fecal sample examination, 76.5% goats were found to be infected with one or more species of endoparasites. In this study, 9 types of helminths ova were identified such as Fasciola gigantica (14.8%), Paramphistomum sp. (28.5%), Schistosoma indicum (3.2%), strongyles (35%), Strongyloides sp. (17.4%), Toxocara spp. (1.5%), Trichuris sp. (4.6%), Capillaria sp. (1.2%) and Moniezia sp. (3.7%). Two types of protozoa were also detected, namely, Eimeria sp. (7.1%) and Balantidium coli (5.5%). Along with these, five species of ectoparasites were found: two species were lice such as Damilinia caprae (13.9 %) and Linognathus vitulli (4.2%), and two species were ticks namely, Haemophysalis bispinosa (21.2%), Rhipicaphalus (Boophilus) microplus (3.6%) and one species was mite, namely, Demodex sp. (2.9%). Mean parasitic burden of Paramphistomum sp. (259.81 ± 3.35) was the highest followed by Eimeria sp. (224.1 ± 16.9) and Moniezia sp. (204.9 ± 19.7). Prevalence of helminths and protozoa was significantly (P<0.01) highest in extensive system (86.1%) followed by semi-intensive (76.3%) and intensive system (57.5%). Ova of Schistosoma indicum was absent in the fecal sample of goats of intensive system. Goats of extensive and semi-intensive systems were 4.6 and 2.4 times more susceptible to helminth infection than those of intensive system. Ectoparasitic infestation was the highest in semi-intensive system (59.7%) followed by extensive system (33.5%) and intensive system (8.2%). In conclusion, the present study suggests that feeding system has a great impact on the prevalence of parasites in Black Bengal goats. Further study can be carried out to determine the effect of parasitism in the production performance of Black Bengal goats. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16470 Progress. Agric. 22(1 & 2): 85-95, 2011